Decentralized or Centralized Governance in Social Dilemmas? Experimental Evidence from Georgia - Mekvabishvili, Rati (Issues in Social Science, 2024)
The vast majority of experimental studies on the effectiveness of punishments in promoting cooperation in social dilemma situation examine decentralized incentive systems where all group members can punish each other. Cross-societal experimental studies suggest that while decentralized incentives can successfully promote cooperation in one society, they fail to do so in another. So, how is social order, as a large-scale cooperation problem among strangers, maintained in such societies? Many modern societies overcome this problem through well-functioning top-down formal enforcement institutions. In the experimental setting of the public goods game, we compare a strong and weak exogenous centralized incentive system with a decentralized incentive system in the case of Georgia. Our experimental evidence suggests that in Georgia, self-governed groups are doomed to suffer from high inefficiencies under a decentralized peer-to-peer punishment incentive system. They are better off when punishment power is given to an external centralized authority that is not exposed to power abuse risks.